Changes in some chemical quality of olive oil during the season in the Al-Jafara region – Libya - السوري احمد السوري; حسني امحمد الدوادي; عبد النبي علي ابوشيتة; المهدي احمد ساسي (African Journal of Advanced Pure and Applied Sciences, 2026)
This study aimed to evaluate the seasonal variations in the chemical quality of olive oil produced in the Al-Jafara region - Libya during the 2025 harvest season. A total of 33 olive oil samples were collected after extraction from mills. during November and December. The analyses included free acidity, peroxide value, and oil extraction yield. The results revealed significant increases (P < 0.05) in free acidity and peroxide value in December compared to November. Mean acidity increased from 1.10% to 1.50%, while peroxide value rose from 11.05 to 18.03 meq O₂/kg. Conversely, extraction yield increased from 21.54% to 24.02%. These findings indicate that fruit ripening enhances oil yield but negatively affects oil quality due to increased oxidation and hydrolysis processes. The study highlights the importance of optimizing harvest timing and improving storage conditions to maintain olive oil quality.